Association between the G252A Tumor Necrosis Factor-β Gene Polymorphism and Medication-Overuse Headache - Ishii, Masakazu (Korean Neurological Association, 2012)
BACKGROUND AND PURPOSE: Migraine patients are particularly prone to the complication of medication-overuse headache (MOH). Although it has been shown that A allele carriers for the tumor necrosis factor (TNF)-β gene G252A polymorphism are at high risk of the development of migraine without aura, the relationship between the TNF-β gene G252A polymorphism and MOH is unknown. We investigated whether the TNF-β gene G252A polymorphism is involved in the aggravation of migraine by overuse of medications. METHODS: Forty-seven migraine patients (6 males and 41 females; age 36.4±10.3 years, mean±SD) and 22 MOH patients (1 male and 21 females; age 39.6±9.9 years) who had migraine were included in this study. The genotype for the TNF-β gene G252A polymorphism was determined by polymerase-chain-reaction restriction-fragment-length polymorphism analysis. RESULTS: The distribution of TNF-β gene G252A genotype frequency differed significantly between migraine and MOH patients (p=0.013). The G/G genotype was carried by 23% of the migraine patients but it was absent in MOH patients. CONCLUSIONS: G/G genotype carriers appear to be less susceptible to the aggravation of migraine by overuse of medications. The G252A TNF-β gene polymorphism may be one of the factors contributing to the complications of MOH in patients with migraine.